Biomorphic SiC: porous SiC and ultrafine SiC powder formation through biomimicking route. (2nd January 2021) - Abdul Karim, Gulnar; Ghosh, Abhijit; Rao, Rekha; Krishnan, Madangopal
ABSTRACT: Natural wood is a ready-to-use template for making porous silicon carbide (SiC) body. Biomorphic β-SiC was synthesised from wood of a mango (Mangifera Indica) tree. Carbon template was made by carbonising this wood at 1000°C in argon gas atmosphere. Thus formed template was repeatedly infiltrated with a mixture of tetraethyl-orthosilicate (TEOS) (in alcohol) and oxalic acid solution (aqueous). Heat treatment at 1600°C for 1 h in vacuum converted the infiltrated template to β-SiC with a complex hierarchical cellular structure- a mimic of the plant structure. To produce phase pure SiC, unreacted carbon (C) and silica (SiO2 ) (if any) were removed by burning in air followed by treating with hydrofluoric acid. Mono dispersed SiC powder having particle size of ∼225 nm has been obtained by crushing, grinding and milling of thus formed biomorphic SiC body. A grinding limit is reported for the first time in SiC system.